中国劳工输入新加坡与「劳动再社会化」因果 ：哲学思辨与田野验证 = The causal analysis of re-socialisation on migratory labour : with reference to Chinese migratory labour in Singapore - 洪于杰 Ang, Yujie (2010)
跨国劳动移民在市场经济全球化的大趋势下成了司空见惯的流动现象。廉价劳动对雇主而言，无疑是一项趋利避害的优化选择，加上目的国出现劳动结构性短缺，中国劳工逐量涌入新加坡亦复如是。有学者认为，对输出国而言，除了汇款流入增值以外，这意味着整体劳动能力与素质将显著擢升，可待劳动队伍回流时直接促激资本经济的发展活络。其次，「再社会化」的思想灌输过程将对劳动者生活产生积极效应。本文研究起因有二：一，尽管学者辩证了关于劳动移民带动经济发展的构成条件，但基本上偏视以物质为基础的因果规律，而抹煞个体主观精神作为调节劳动关系与影响总体利益方向的因果角色；二，学者倾向功利价值判断而简化了「劳动再社会化」作为劳动关系的精神互动性质，并未对当中的因果联系探赜索隐。本文将通过「精神镶嵌」的研究方法针对「劳动再社会化」作因果分析。当中的概念架构包含了雇主与劳动主体在劳动关系中不同阶段的个体人格意向，并探讨「劳动再社会化」与经济发展（总体利益）之间的构成条件和定律，再将其中的分析内容归纳为「劳动再社会化」的三项理论原则。最后，本文就新加坡的中国劳动移民为研究对象，通过田野调查来分析与探讨「劳动再社会化」的实践因果.Trans-national labour migration has become the ubiquitous phenomenon under the globalising trend of market capitalism. Chinese labour migration to Singapore continues to augment due to the reciprocal demand and supply continuity. In addition to the impasse where the labour receiving country experiences structural labour shortage, cheap transient labour remains to be a profit-maximalising preference to the employers. Academics perceive the practice of sending labour to be a stimulus for capital accumulation in the form of remittances and economic development in the labour sending country. Migratory labour will acquire new technical skills and knowledge, following which the resultant labour power boost is thought to engineer the developmental process given the circumstances of return migration. Additionally, labour re-socialisation, a social process that forms the crux of labour relations, is assumed to have achieved positive outcomes on migratory labour.